The Habituation of Dhuha Prayer and Qur'an Recitation as an Effort to Shape Students' Morality - Saini, Mukhamat; Rahmawati, Lilis; Munawaroh, Hidayatul (STAI Miftahul Ula Nganjuk, 2023)
The implementation of religious practices in schools, such as performing Dhuha prayer and reading the Qur'an, is often carried out with the aim of instilling good morals and character in students. Similarly, at MA Az-Zain, the habituation of Dhuha prayer and Qur'an recitation is employed as a strategy to further improve the students' moral character. This study utilizes a qualitative research method to describe the issues and focus of the research. Data collection was conducted through observation, interviews, and documentation. The findings of this study conclude that: (1) The implementation of the Dhuha prayer habituation program at MA Az-Zain is carried out daily at the start of the school day, consistently. The Dhuha prayer is performed both communally in the mosque and individually, (2) The habituation program for Qur'an recitation at MA Az-Zain is conducted daily after the Dhuha prayer, in the classroom, just before the first lesson begins, (3) The habituation programs of Dhuha prayer and Qur'an recitation at MA Az-Zain can shape the character of students, as evidenced by the positive behaviors observed following the regular practice of these activities